Switched optimal robust control of a 3-DOF helicopter subject to a critical fault - Assuncao, Edvaldo [UNESP]; Teixeira, Marcelo C. M. [UNESP]; Buzachero, Luiz F. S.; Da Silva, Emerson R. P. (Institute of Electrical and Electronics Engineers (IEEE), 2017)
This paper proposes an improved technique for the stabilization of continuous-time, switched controlled linear systems with decay rate performance index and optimization of the controller's norm. This technique is of closed loop nature (trajectory dependent) and is designed from the solution of Lyapunov-Metzler inequalities from which the stability condition (including chattering) is expressed. The performance index used here is the decay rate that aims to reduce the system's settling time. The other important tool used is the optimization of the controller's norm that aims to reduce the gains and facilitate its application. A practical implementation of the improved technique was made in a Quanser's 3-DOF helicopter subject to a structural fault in the back engine, which was addressed as a polytopic time-varying uncertainty.